Pengaruh Promosi dan Fitur Seabank terhadap Kepuasan dan Loyalitas Pelanggan Mahasiswa/i FEBI UIN SMH Banten - Nasywa Nabil Oktaviani; Ratu Eprilla Maharani; Rifda Amaliatun Nisa; Hadi Peristiwo; Wahyu Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze the influence of Seabank promotions and features on the satisfaction and loyalty of FEBI UIN SMH Banten students. Seabank is a digital banking application that provides convenience and comfort in managing your finances anytime, anywhere, from saving to doing various things on your smartphone. PT Seabank Indonesia (Seabank) was previously known as PT Bank Welfare Economics (BKE). After receiving ownership of the Shopee Company, the company name was changed to Seabank on February 10 2021. Based on KEP-12/PB.1/2021 Deputy Commissioner for Banking Control (OJK) of the Financial Control Authority regarding the allocation of use of activity permits in the name of PT. Economic Welfare Bank establishes a business license in the name of PT Bank Seabank Indonesia. The focus of this research is to examine Seabank's offers and features as independent variables and customer satisfaction and loyalty as dependent variables. This study uses a quantitative approach. The main data used consisted of 30 respondents. Apart from that, this research material was processed using the SPSS version 25 computer program. The research results show that Seabank promotions and features do not have a positive impact on customer satisfaction and loyalty, especially for FEBI UIN SMH Banten students.